Multi-Beam Light-Matter Interactions in Epsilon-Near-Zero Materials and Nanoscale Metasurfaces - Lim, Theng Loo (Université d'Ottawa / University of Ottawa, 2023)
Light-matter interactions are essential for the development of many modern technologies and for fundamental science. Hence, many recent efforts have focused on understanding light-matter interaction in exotic classes of materials, particularly in subwavelength (nanometre scale) regimes. This Master's thesis focuses on two different types of materials whose interaction length is typically in the nanoscale. First, we studied and observed the energy transfer between two ultrashort beam pulses in the epsilon-near-zero (ENZ) spectral range of a material, classified where the real part of the material's electric permittivity has a magnitude much less than 1. Typically, such energy transfer in ordinary materials (such as fused silica) requires different wavelengths of both beams interacting in the material. However, ENZ materials have an unprecedentedly high optical nonlinearity, leading to self-manifesting energy transfer. This self-manifesting effect occurs in ENZ material due to the effective frequency shift known as adiabatic frequency conversion (AFC) caused by a significant change of refractive index from its large optical nonlinearity. Second, we studied a class of materials known as metasurfaces, which are built from an array of artificial engineered nano-antennas. Metasurfaces can enable custom wavefront control or the engineering of coupling to designated surface modes, which is not possible for naturally occurring optical surfaces. In this thesis, we developed a design scheme for constructing a metasurface that generates multiple lattice resonances at desired wavelengths. Such a design scheme is possible because we arranged the nano-antennas using Fourier analysis. This flexible scheme produces a metasurface design directly from the desired distribution of resonances.
Keywords: light-matter interaction